Effect of Psychological Well-Being and Mental Health on the Student’s Educational Achievement with the Mediating Role of Resiliency - Khaleghkhah, Ali (International Review of Management and Marketing, 2017)
One of the concerns of parents and education today is students’ educational achievement since it is believed that success in education can partially predict individual success in the future. Therefore, the aim of this study was to investigate the effect of psychological well-being and mental health on high school students’ educational achievement with the mediating role of resilience. The study population consisted of all high school students in Urmia city in 2015-2016 school year. The samples included 320 individuals who were selected using convenient random sampling method. Four questionnaires were employed for data collection, including Reef’s psychological well-being questionnaire (1980), General Health Questionnaire (GHQ-28), Connor-Davidson’s Resilience Questionnaire (2003) and the students’ achievement scores. The results indicated the fitness of conceptual model and its approval for public high school students in Urmia city. The direct effect of psychological well-being variable on resiliency (.68) considering the t-value (t = 6.42) at the confidence level of .01 is significant. The direct effect of Mental health on resiliency (.69) considering the t-value (t = 7.12) at the confidence level of 0.00 is significant. The direct effect of resiliency on the educational achievement (.54) and considering the t-value (t = 5.27) at the confidence level of .02 is significant. The indirect effect of psychological well-being on educational achievement with the value of .29 and the indirect effect of mental health on educational achievement with the value of .37 are significant. It is recommended that the findings of this study, which are indicative of paying more attention to meet the students’ mental health in many ways than ever before, be used to identify the students at risk for clinical evaluation and also more comprehensive and better intervention programs be designed and implemented to decrease students’ psychological and educational achievement problems. Keywords: Psychological well-being, mental health, Resilience, Educational achievement, Students. JEL Classifications: I12, I2